PENINGKATAN KEMAMPUAN KEPALA TK SEBAGAI SUPERVISOR MELALUI SKILL TRAINNING FOR THE JOB DINAS PENDIDIKAN KECAMATAN BULUTAHUN 2015 - Subarjo . (Universitas PGRI Semarang, 2015)
Supervisory Unit Kindergarten of sub-district Bulu Abstrak Educational Research Office is done at the Sub-District Education Officein?é?á Bulu,District : Temanggung, the subject and object of study is a number of 15 Head of kindergarten. The study aims to determine the increase skill/capacity of kindergarten as Supervisor, at the District Education Office of Bulu, and to knowthe?é?á activity and?é?á spirit of the Head Office of Head of Kindergarten at The Educational Unit, Sub-District Bulu during joining the Skill Training For The Job. The research analysis uses comperative discriptive?é?á and procentage discriptive. Results of the study showed that the knowledge aspects and concepts of supervision, head of the kindergarten gained an average score of 46.66, or (D) the category of